SUSTAINABLE PILAR OF RURAL TOURISM DEVELOPMENT - Harne julianti Tou; Melinda Noer; Helmi (Fakultas Teknik Sipil dan Perencanaan. Universitas Bung Hatta, 2022)
Tourism is not only done in urban areas but also has been in great demand in the countryside. This is due to the beauty of nature, cultural uniqueness, and other characteristics in rural areas that attract visitors. Besides aiming to reduce the fatigue of activities in the city, tourists also want to experience nature and the life of rural communities. This literature study research seeks to identify the main pillars of sustainable rural tourism development. Sustainable rural tourism development is the development of the tourism sector in the village by observing the sustainability of tourism, such as efficient use of environmental resources while preserving natural heritage and biodiversity, including respecting the socio-cultural authenticity of the local community in terms of inter-cultural tolerance and should provide socio-economic benefits to all stakeholders, using qualitative descriptive methods. The writer analyzed the objects of the study in terms of tourism development, rural tourism, sustainable rural tourism development, and the role of stakeholders in rural tourism development. The main pillars found are culture and community participation (socio-culture), ecology (environment), and policy (politics).